Incidence and impact on prognosis of heart failure in Middle Eastern patients undergoing percutaneous coronary interventions - Ayman J Hammoudeh (Asian Journal of Medical Sciences, 2017)
Background: Heart failure (HF) is a serious complication of percutaneous coronary intervention (PCI) that adversely impacts survival and quality of life.